Effect of Lime Content, Curing Temperature, and Aging Condition on Low-Alkaline Concrete - Pour, Mahdi Parsa; Sharghi, Reza Shaban; Nejati, Faezeh; Najafi, Elmira Khaksar (UI Scholars Hub, 2023)
This study determines how curing temperatures, aging condition, and hydrated lime contents affect the unconfined compressive strength (UCS), modulus of elasticity, and workability of low-alkaline concrete. Samples were prepared in two different groups to determine the optimum hydrated lime content and aging conditions to assess the mutual effect of NaOH molarity and curing temperature, that is, 70 °C for 48 h or room temperature, on samples with and without lime. The results showed that the increase in hydrated lime content affected alkali concentration. The samples with lime exhibited a clear peak in UCS (6 M NaOH) compared with the continuous increase for the samples without lime. Lime content had a positive effect on eliminating heat curing and prolonging aging time to enhance the Young’s modulus and compressive strength. This result is promising for in-situ concreting. Similar to the effect of alkali concentration, lime contributed to the loss in slump value. The scanning electron microscopy images showed the formation of N-(C)-A-S-H gels as the main reaction products. Moreover, internal cracking contributed to the lower UCS of samples with 9 M NaOH compared with those with 6 M NaOH.